Pemanfaatan Teknologi Pendidikan Kawasan Pengembangan dalam Membuat Media Pembelajaran - Nurkamilah, Siti; Putri, Diah Ika; Muthmainnah, Rifaatul Ika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this research is to find out how the utilization of education technology development area in the manufacture of learning media by certified teachers in Garut Regency, West Java. This research is qualitative research using descriptive method. The research subjects involved were ten certified teachers. As a result of the research, all teachers have utilized educational technology in the manufacture of learning media, especially during the COVID-19 outbreak which has made the government implement distance learning, so that teachers are required to understand and master a variety of interesting learning media creation. Most teachers take advantage of computer-based media both online and offline, because it is more accessible to students. In addition, audio visual media is also the most used media by teachers, because it is considered to be a medium that can interest students in learning. In conclusion, the use of learning media by certified teachers mostly leads to the utilization of multimedia computer-based technology with more choice on audio visual materials both online and offline in providing learning materials, taking into account aspects of the availability of supporting facilities and infrastructure in schools. Keywords: Learning Media, Teaching Materials Development, Educational Technology.